Performance Estimation: CCL WPT Topologies with Helical Coils - Chien-Lung Chen; Chung-Wen Hung (Energies, 2022)
The radius of the coil, the number of turns of the windings, and the parasitic resistances of energy-storing elements affect the performances of wireless power transfer systems. We aimed to study the effects of coil parameters on a wireless power transfer system with the capacitor–capacitor–coupling coil (CCL)-based circuit using numerical simulations. The power transfer system topologies, including series–CCL (S–CCL), CCL–S, and CCL–CCL, were studied vis-à-vis coil parameters. The helical coil and the system topologies were modeled using MATLAB, and the performances of the topologies were examined in comparison to the series–series (S–S) topology. The variables used in the simulations included the radius and number of turns, the parasitic resistance that was merged in the impedance, and the reactance of energy-storing elements. Subsequently, the performances of the topologies were estimated by numerical simulations under several circumstances. The simulation results showed that the parasitic resistance of the coupling coil affects the performances of the topologies directly. The coupling coils with smaller geometries are beneficial to power transfer in the wireless power transfer system and may further contribute to miniaturization.